Time-resolved measurements of extreme ultraviolet (EUV) emission, from EUV-induced He, Ne, and Ar plasmas. (19th March 2019) - Bartnik, A.; Fiedorowicz, H.; Wachulak, P.; Fok, T.
Abstract: Irradiation of gases with intense pulses of extreme ultraviolet (EUV) can result in the formation of low-temperature plasmas. During the time of irradiation, various non-thermal processes driven by the EUV photons and photoelectrons take place, leading to the creation of excited states of atoms and ions. Fast relaxation of these states should result in EUV emission within a time comparable to the driving EUV pulse. On the other hand, from our earlier works, a time duration of the emission in an optical range is over an order of magnitude longer. It can be thus expected that the time of EUV emission can be also relatively long. In this work, time-resolved measurements of the EUV emission from low-temperature plasmas induced in He, Ne, and Ar gases were performed. Due to a low intensity of the emitted radiation, a specially prepared detection system, based on an EUV collector and an EUV sensitive photodiode, was employed. In all cases, a time duration of the EUV emission was much longer compared with the driving EUV pulse. Time profiles of the corresponding signals were specific for particular gases. In case of He and Ne plasmas, these time profiles varied with initial densities of gases to be ionized. The corresponding dependence was especially visible in case of plasmas induced in helium. In case of Ar plasmas, such dependence was not revealed.